2017
DOI: 10.3201/eid2302.160751
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and New Lineages of Dengue Virus Serotypes 3 and 4 in Returning Travelers, Germany, 2006–2015

Abstract: During 2006–2015, we analyzed 70 dengue virus (DENV) strains isolated from febrile travelers returning to Germany. High genetic diversity, including multiple co-circulating DENV lineages and emerging new lineages of DENV-3 and DENV-4, was demonstrated. Our passive surveillance system based on returning travelers yielded substantial information on DENV diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Between 2008 and 2012, however, DENV‐1 become the dominant serotype in most Indonesian regions (Table ). Data of traveller‐associated dengue from Australia, Taiwan, Germany, and Romania support this finding. A comprehensive study conducted in Surabaya found that the serotype shift from DENV‐2 to DENV‐1 occurred in late 2008 .…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…Between 2008 and 2012, however, DENV‐1 become the dominant serotype in most Indonesian regions (Table ). Data of traveller‐associated dengue from Australia, Taiwan, Germany, and Romania support this finding. A comprehensive study conducted in Surabaya found that the serotype shift from DENV‐2 to DENV‐1 occurred in late 2008 .…”
Section: Resultsmentioning
confidence: 55%
“…A full assessment of the 120 references resulted in the exclusion of 53 references due to the following: full texts were unavailable, and the available abstracts did not include adequate information to satisfy our outcome, the full text did not include adequate or complete serotype data, and nonstandard methods were used for serotyping. This resulted in 67 eligible studies, of which 13 references were from national journals . An additional 11 studies were included from reference list .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations